PENGARUH EDUKASI MEDIA AUDIOVISUAL DAN BOOKLET TERHADAP PERILAKU WASPADA COVID-19 - Winanda Rizki Bagus Santosa; Wildan Akasyah (Jurnal Keperawatan Priority, 2023)
Covid-19 is a disease that has a large impact on death with a large number in the world including Indonesia and East Java. Alert behavior towards Covid-19 by maintaining health protocols and increasing knowledge through educational audiovisual media and booklets can increase alert behavior and an effort to prevent transmission of Covid-19 in the community. This study aims to determine the effect of audiovisual media and booklets on Covid-19 alert behavior. This research method is experimental with the research design using one group pretest and posttest. The sampling technique is accidental sampling. This research was conducted for four days on patients who came to Health Center X, Kediri district. A sample of 34 respondents with research inclusion criteria. This research was given a pre-test questionnaire with a total of 10 questions about Covid-19 awareness, then provides education using audiovisual media and booklets, and then gives a post-test. Test the validity with the Pearson test and the reliability using the Cronbach Alpha test with valid and reliable results. This study used the Chi-square test. From the results of this study, there was an effect of educational audiovisual media and booklets on covid-19 alert behavior with a P value of 0.01. There is a difference in the average value before being given education through audiovisual media and booklets is 31.20% and after being given education through audiovisual media and booklets is 43.71%. These results show an increase of 15. Audiovisual media and booklets have an educational effect on Covid-19 alert behavior.